Pesticide Emergencies: Fires and Spills - Frederick M. Fishel (EDIS)
Although accidents and emergencies involving pesticides are rare, unfortunately they do occur. Pesticide fires or spills can result in water, soil, and air contamination; damage to plants; injury to livestock, wildlife, or pets; and can endanger the health of the applicator and other people. Those using pesticides must be prepared to respond to fires and spills as emergencies and act promptly and correctly. This 6-page fact sheet explains how to reduce fire and spill hazards and what to do if a fire or spill should occur. Written by Frederick M. Fishel, and published by the Agronomy Department, December 2015.